Philippine motion pictures, 1908-1958 a checklist of the first fifty years - Momblanco, Maria Carmencita A. (1979)
This bibliography covers the first fifty years of motion pictures produced and exhibited in the Philippines, 1908-1958, and included 1,372 films. It lists only feature films, presenting film credits as they were found in printed sources primarily newspapers, weekly magazines, monographs about movies, producers' brochures and lists, and souvenir programs celebrating annual awards which were available at the time of compilation.